The Perspective of Researchers on the Challenges of Research in Brazil (Educação e Pesquisa, 2020)
The Brazilian scientific and technological development has presented important advances in the last decades. However, several obstacles still limit the impact of Brazilian research on the international scenario. Thus, the objective of this study is to identify the main challenges of scientific and technological research in Brazil, analyzing latent factors, according to the perception of researchers working in Brazilian public universities. For this purpose, an exploratory-descriptive study was carried out, combining qualitative (content analysis) and quantitative (factor analysis) techniques, employing data collected through 16 interviews and 722 questionnaires filled out by researchers working in postgraduate programs (master’s and doctorate) of Brazilian public universities. The results indicated the presence of eleven challenges, which can be grouped into three latent factors: (i) research environment, represented by working conditions regarding access to resources, deficient infrastructure, high bureaucracy and work overload; (ii) research practices, represented by the low interaction of researchers with each other and with the demands of society, low dissemination/appropriation of the knowledge produced and excessive valuation of scientific articles and (iii) training and qualification of human resources, represented by the lack of commitment and qualification of researchers, besides the low relevance of the research developed. These results are important for the identification of the main obstacles of research in Brazil, allowing new reflections for the advancement of the National System of Science, Technology and Innovation (SNCTI).